(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2021)
The objective of this study was to evaluate the performance and quality of eggs of laying hens of the Hisex Brown signage submitted to diets with the inclusion of pequi pulp flour. The experiment was conducted with a total duration of 63 days (3 periods of 21 days each), and 240 birds of the commercial lineage Hisex Brown were used at 35 weeks of age distributed in 30 experimental plots, with 2 birds in each, totaling 8 birds per plot. A completely randomized design was used with 5 treatments (inclusions of 0%; 0.125%; 0.250%; 0.375% and 0.5% of pequi pulp flour). The variables of egg performance and quality were submitted to linear and quadratic regression analysis at the level of 5% probability. No significant differences were observed for the inclusion levels of pequi pulp flour. The flour levels of pequi pulp tested in the present study were not sufficient to demonstrate improvements in the productive performance of birds and egg quality. Further research with higher inclusion percentages is necessary to evaluate the effectiveness of this natural supplement.